Peranan Distribusi Dana Zakat Produktif Baitul Maal Wa Tamwil dalam Meningkatkan Modal Usaha UMKM - Silfa Salsabela; Hendrawati Hendrawati (Lembaga Penelitian Universitas YARSI, 2024)
This research focuses on exploring a model for the productive distribution of zakat as a means to boost business capital, particularly for MSMEs. The qualitative method employed involves primary data from direct interviews with various stakeholders, including supervisors, administrators, YBM BRI staff, and MSME actors located on Jl Teen 2 Jatinegara Kaum Pulogadung, East Jakarta. The analytical approach comprises gathering data through interviews, condensing insights from these discussions, and presenting conclusive findings. Prior to receiving assistance from the BRI YBM program, mustahik recipients faced challenges in acquiring business capital due to escalating costs of basic materials. The distribution of productive zakat funds through institutions like Baitul Maal Wa Tamwil can significantly impact managerial effectiveness in bolstering MSME business capital. Several managerial influences have been identified, such as conducting risk and financial assessments. BMT managers must carefully assess risks associated with receiving zakat funds and their distribution to MSMEs. Additionally, there's a focus on recipient selection, training, and mentoring. This approach showcases how well-managed zakat distribution, especially when channeled effectively through institutions, can alleviate economic shortages by empowering MSMEs with essential capital.